Cytotoxic effects of heavy metals on functional attributes of boar sperm: an in vitro study - Kadirvel, Govindasamy; Diengdoh, Jasmine; Deori, Sourabh; Dewry, Raju Kumar; Abedin, Sayed Nabil; Moirangthem, Prabha (Frontiers in Environmental Science, 2023)
Objective: Reproductive toxicology is a field that deals with the effects of heavy metals on various aspects of reproduction, including sperm count, motility, viability, spermatogenesis, follicular atresia, hormonal imbalance, delayed oocyte maturation, and more. The present study was carried out to study the effect of heavy metals viz., Arsenic (As), Lead (Pb) and Fluoride (F) on boar sperm quality parameters in vitro. Materials and Methods: Forty (40) ejaculates from six (6) boars, averaging 8 ejaculates per boar were collected with the gloved hand technique using a dummy sow. Six (6) different As and Pb concentrations (5, 10, 25, 50, 100, and 200 µM) and F concentrations (5, 10, 25, 50, 100, and 200 mM) were chosen respectively for the in vitro study. The ejaculates were coincubated with heavy metals of different concentrations at different incubation periods (0, 0.5 and 1h) and sperm functional attributes viz., sperm progressive motility, viable sperm and intact membrane, and sperm mitochondrial membrane potential (MMP) were assessed. The combined effect of heavy metals on sperm functional attributes was also evaluated at different doses (5, 10, 25, 50, 100 and 200 µM/µM for As-Pb; 5, 10, 25, 50, 100 and 200 µM/mM for As-F and 5, 10, 25, 50, 100 and 200 µM/mM for Pb-F). Results: The present study revealed a highly significant (p<0.001) decrease in sperm progressive motility, viable sperm and intact membrane, and sperm MMP in treated groups with heavy metals with different incubation periods and longer the incubation time greater is the toxicity. There was also a significant (p<0.05) decrease in sperm motility, membrane integrity and MMP in the combined heavy metal treated groups (As-Pb, As-F and Pb-F) as compared to control in different incubation periods. Significant (p<0.05) reduction in sperm quality attributes was recorded even at the lowest concentrations in the heavy metal combination groups.It can be concluded that As, Pb and F are toxic to boar spermatozoa in vitro causing reduction in sperm functional attributes in a dose and time dependent manner.